Manajemen Pengolahan Sampah Terpadu dalam Meningkatkan Pendapatan Masyarakat di Kecamatan Tampan Kota Pekanbaru - Tuti Khairani Harapan (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2017)
Pekanbaru City as a metropolitan city that continues to increase the population of the population, thus causing an increase in the amount of waste generated every day. This certainly requires the City Government of Pekanbaru especially Tampan district which has a very large area and a very large population in order to be able to manage the existing waste in this area. But in reality, this has not been done optimally. Sudjana (2004: 17) defines that management or management is the ability and special skills to do something good activities with others or through others in achieving organizational goals. This research aims to know and analyze the management of integrated waste processing, the inhibiting factor, and the integrated waste management in improving the right people economy in Kecamatan Tampan Pekanbaru City. The method of analysis used in this study is qualitative and quantitative. The result of this research is that integrated garbage management in improving people's economy in Kecamatan Tampan Pekanbaru has not been implemented maximally. This is due to factors of sources and types of waste, behavioral factors of society (social and cultural), institutional factors and facilities and infrastructure. So it is a very necessary application of integrated waste processing management in improving the society's economy in Tampan district of Pekanbaru city through the application of Community-based Processing.